Informação orgânica como insumo estratégico para a tomada de decisão em ambientes competitivos: estudo nas empresas do setor varejista situadas na cidade de Marília/SP - Lousada, Mariana; Valentim, Marta Lígia Pomim [UNESP] (My University, 2012)
The focus of this research is centered on organic information production, sharingand use on the enterprise decision making process. The information on the present economy becomes value source for organizations. The organic information is produced on the organization s internal environment been a product of the activities made by execution its functions. Knowing the elements that involve this process gives a great help to managers once the decision making process is permeated by conflicts and different perceptions. Therefore, the organic information can reduce these conflicts on organizational contexts, because it reduces the uncertainness, propitiates more security and more trustworthiness to the decision making process, besides it gives dynamism to people s time involved on the process. The investigated universe was composed by the companies affiliated to Construnova Net, from construction material segment, located at Marilia Region s cities, Sao Paulo State, because it is an important segment which influences the local and regional economy. The methodological proceedings used are based on the qualitative approach which method is related to descriptive and exploratory research. As data collecting instruments were elaborated a structured questionnaire with closed questions and an interview s syllabus which contents are related to the research s aims. As analysis proceedings for the collected data and also to consider the qualitative approach it was chosen the Contents Analysis method from Bardin and more specifically the Categorical Analysis . Consequently, we conclude that it is deficient in production of organic information, or to produce documents that prove and control the activities that are developed within the organization is not satisfactory. The decision usually is not subsidized by organic information. Accordingly the study points out the deficiency of the perception of the importance of the organic type information as an aid to decision making and al

O foco desta pesquisa centra-se na produção, compartilhamento e uso da informação orgânica no âmbito do processo decisório empresarial. A informação na economia atual tornou-se fonte de valor para as organizações. A informação orgânica é produzida no ambiente interno da organização sendo produto das atividades desempenhadas no exercício de suas funções. Conhecer os elementos que envolvem esse processo auxilia enormemente os gestores, visto que o processo decisório é permeado de conflitos e diferente percepções. A informação orgânica, portanto, pode reduzir esses conflitos em contextos organizacionais, pois reduz a incerteza, propicia mais segurança e maior confiabilidade ao processo decisório, além de dinamizar o tempo das pessoas envolvidas no processo. O universo pesquisado foi constituído das empresas afiliadas a Rede Construnova, do segmento de material de construção, situada nas cidades da região de Marília, Estado de São Paulo, pois se configura em um segmento importante que influencia a economia local e regional. Os procedimentos metodológicos utilizados se alicerçaram na abordagem qualitativa cujo método refere-se à pesquisa descritiva e exploratória. Analisou-se de que forma a informação orgânica atua no processo decisório do universo pesquisado, a fim de verificar os elementos teóricos e aplicados para sua consolidação como fonte de recurso estratégico. Pelo exposto, o estudo aponta a deficiência da percepção da importância das informações do tipo orgânica como subsídio ao processo decisório e, também, como recurso estratégico.
Organic input information as a strategic decision in competitive environment: study companies in retail sector located in the city of Marilia/SP.
Keywords: Informação Orgânica; Informação Arquivística; Processo Decisório; Modelos de Tomada de Decisão; Ambientes Empresariais